Ultra-sensitive nanometric flat laser prints for binocular stereoscopic image - Dejiao Hu (Nature Portfolio, 2021)
The authors demonstrate fidelity colour prints and binocular stereoscopic images in multilayer MoS2 integrated on an Au substrate, showing nanometric layer sensitivity in the Fabry-Perot resonance changed by a facile laser recipe.